2010
DOI: 10.1001/archoto.2010.34
|View full text |Cite
|
Sign up to set email alerts
|

Correlations Between Endoscopy Score and Quality of Life Changes After Sinus Surgery

Abstract: Objective To assess whether change in endoscopy score correlates with change in health-related quality of life (HRQOL) following endoscopic sinus surgery (ESS) for chronic rhinosinusitis (CRS). Setting Tertiary rhinology clinic Patients One hundred two adult patients, with and without nasal polyposis, who elected to undergo ESS and were followed for 12 ± 2 months postoperatively. Intervention Patient characteristics and Lund-Mackay computed tomography scores were recorded preoperatively. Lund-Kennedy end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
49
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 24 publications
6
49
1
Order By: Relevance
“…Unfortunately, at best, endoscopic scoring systems only weakly correlate with current QoL 64,67 and postoperative gains in QoL. 69 Although there is room for refinement of endoscopic scoring, endoscopic exams likely provide only a portion of the data required to accurately predict symptomatology.…”
Section: Ivc Measurement Of Disease Severitymentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, at best, endoscopic scoring systems only weakly correlate with current QoL 64,67 and postoperative gains in QoL. 69 Although there is room for refinement of endoscopic scoring, endoscopic exams likely provide only a portion of the data required to accurately predict symptomatology.…”
Section: Ivc Measurement Of Disease Severitymentioning
confidence: 99%
“…75,1347 Despite this, clinicians see significant improvement in objective findings regardless of polyp status, indicating that ESS is important in bringing the objectively measured inflammatory processes under control. 69,75,1347 Patients with CRSwNP tend to have better baseline QoL relative to patients with CRSsNP; however, specific symptoms such as nasal airway obstruction and olfactory disturbance tend to dominate CRSwNP. 75,77,868,1347,1348 Interestingly, patients with CRSwNP have the greatest improvement in QoL following ESS despite their relatively better baseline QoL.…”
Section: Ess Outcomes Differences Between Crswnp and Crssnpmentioning
confidence: 99%
“…By McNemar test* [11][12][13][14][15] Our study shows that most of the patients (40%) were among the age group 25-34 years, followed by age group 35-44 years (30%). This age distribution is comparable to study done in the USA in 2010 who found (30%) of patients belong to age group 21-30, and (27%) belongs to age group 31-40.…”
Section: Symptoms Distributionmentioning
confidence: 61%
“…The main goal in the treatment of a patient with CRS should be to decrease nasal blockage and nasal discharge complaints, which have a signifi• cant correlation with the life quality of the patient [11]. Objective and subjective methods can be used in the evaluation of treatment [7]. Although medical and surgical reduction of polyps, discharge, edema and crusting significantly improves the inflammatory process and the corresponding endoscopy score, these improvements can explain only a small percentage of the association with patient based HRQoL and sinonasal symptom burden.…”
Section: Resultsmentioning
confidence: 99%
“…There are limited numbers of papers about the impact of ESS on quality of life in the literature. It is important to use disease specific health related quality of life (HRQoL) surveys when determining the success of ESS [7]. The reliability of this survey must be proven.…”
mentioning
confidence: 99%